Construction quality management - Tang, S. L. (Siu-lam) (Construction and real estate series., 2005)
This book examines the various quality management systems applied to the construction industry in Hong Kong and other parts of the world. Hong Kong's experience is particularly important because it plays a leading role in construction quality management globally.